2004
DOI: 10.1159/000080915
|View full text |Cite
|
Sign up to set email alerts
|

‘Interapy’ Burn-out: Prävention und Behandlung von Burn-out über das Internet

Abstract: ‘Interapy’ Burnout: Prevention and Therapy of Burnout via the Internet Background: In recent years a lot of computer-driven self-help programs have been developed in which no client-therapist interaction whatsoever takes place. These programs have yielded varying successes. The Internet offers new possibilities, including treatment programs in which clients do interact with their therapist, without the two ever meeting face to face. The therapist responds to client input and vice versa. This is the essence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
0
10
0
4
Order By: Relevance
“…This method comes close to the therapist-supported writing therapy, an approach that has been used in the treatment of various other disorders with good results (including posttraumatic stress disorder [24,25,26], complicated grief [27,28], social phobia [29,30,31], panic disorder [32,33], generalized anxiety disorder [34,35], depression [36,37] and burnout [38]). However, therapist-supported writing therapy goes beyond a self-help approach with therapist contact.…”
mentioning
confidence: 99%
“…This method comes close to the therapist-supported writing therapy, an approach that has been used in the treatment of various other disorders with good results (including posttraumatic stress disorder [24,25,26], complicated grief [27,28], social phobia [29,30,31], panic disorder [32,33], generalized anxiety disorder [34,35], depression [36,37] and burnout [38]). However, therapist-supported writing therapy goes beyond a self-help approach with therapist contact.…”
mentioning
confidence: 99%
“…This CBT programme was found to be effective in face-to-face treatment [29, 30]. In a randomised controlled trial, the Interapy CBT programme for work-related stress was found to be more effective than a control condition consisting of psycho-education only [31]. …”
Section: Computer-guided Therapy and Tele-therapymentioning
confidence: 99%
“…Im Gegensatz dazu werden in der Psychotherapie Erwachsener Computer und Internet immer häufiger zur Unterstützung gerade kognitiv-verhaltenstherapeutischer Behandlungsprogramme eingesetzt. Es gibt internetbasierte Programme zu Essstörungen [Celio et al, 2000], posttraumatischer Belastungsstörung [Lange et al, 2003[Lange et al, , 2004, Angststö-rungen [Marks et al, 2003] und Depressionen [Andersson et al, 2004;Proudfoot et al, 2003]. Diese Programme bestehen häufig aus einer Kombination von direktem Kontakt mit dem Therapeuten und einem computerunterstützten Selbsthilfeprogramm [s.a. Knaevelsrud et al, 2004].…”
Section: Psychotherapie Am Computer?unclassified